Association between procrastination and learning strategies in medical students in a hybrid problem-based and lecture-based learning curriculum - Manuella Meireles Pereira; Marcos Kubrusly; Ana Beatriz Teófilo Macedo dos Santos; Matheus do Nascimento Oliveira; Lucas Olímpio Coimbra; Hermano Alexandre Lima Rocha (BMC Medical Education)
Abstract Background Procrastination is characterized by the deliberate postponement of assigned educational tasks and is correlated with low academic achievement and depression. Concern about procrastination is particularly high among medical students, as it has a strong association with aspects such as low self-efficacy, lack of organization, low intrinsic motivation, inefficient effort regulation and time management problems. On the other hand, it was found that students' use of study strategies is significantly related to better academic results. The relationship between students' tendency to procrastinate and the adoption of effective study strategies remains little explored, leaving a critical space for investigation. This study aims to fill this gap by exploring how procrastination affects the selection and effectiveness of study strategies adopted by students. Methods This cross-sectional study was conducted in Brazil and included medical students from the first to the seventh semester of the Unichrsitus Medical School. The validated procrastination scale and the Learning and Study Strategies Inventory were used. Generalized linear regression multivariate models with robust errors were used to verify the association between the study variables. Results 447 students participated, 70.2% of whom were female, with an average age of 23 years. The domain of “study aids” scored higher among younger students, who self-referred as black and who studied in private schools prior to the Medical School. Higher procrastination scores were statistically associated with higher main idea selection, concentration, time organization and anxiety scores and with lower study aids and study preoccupation scores (p values < 0.05). In addition, active methodology was associated with higher scores in the domains of study aids and time organization. Conclusions Procrastination is associated with the study strategies used by medical students, which can be modified through training and ultimately improve their performance. Students in traditional models, who are older, white and from public schools may especially benefit from this training.